Factors which influence student satisfaction among international postgraduate students in Universiti Utara Malaysia - Khaled Mohamed Helmy, Aya (2016)
In today’s competitive environment student satisfaction become a significant factor for higher education. This was because satisfied students could attract new students and help to retain existing students. Despite importance of student satisfaction in higher education institutions, limited studies have been done on student satisfaction in Malaysian higher education. The declining number of international postgraduate students in UUM had raised researcher interest to make the study. The objective of this study was to examine the influence of some factors like accommodation, cafeteria food service, transportation and teaching quality on student satisfaction among international postgraduate students in Universiti Utara Malaysia (UUM). The survey method utilizes the questionnaire for data collection process. Pearson Correlation and Multiple Regression were used for data analysis through SPSS version The survey questionnaires were distributed to 291 respondents however only 192 questionnaires were received back or 65.9 percent. The main finding of study showed there were significant relationships between accommodation, cafeteria food service, teaching quality and student satisfaction. Transportation, however, did not show any significant relationship with student satisfaction